A new approach to estimate damage in concrete beams using non-linearity. (15th October 2016) - Hanif, Muhammad Usman; Ibrahim, Zainah; Jameel, Mohammed; Ghaedi, Khaled; Aslam, Muhammad
Highlights: Lack of globally applicable damage detection method in RC beams. Constitutive relations for damage in concrete beams. Method proposed for damage detection without requiring undamaged state. Nonlinear damage detection in RC beams through simulations. This model is capable of detecting damage in inverse problem solving. Abstract: Damage detection in concrete structures has become a serious problem for engineers. Despite spanning almost half a century, the research on this subject has proven a lack of globally applicable damage detection methodology that can detect damage without the use of parameters from the undamaged state. Therefore, there is a vital need to detect damage without the use of data from the undamaged state of the structure. This research focuses on integrating the power of commercial finite element software using modal dynamic analysis to detect damage in concrete structures. To achieve this goal, a simulation based damage detection method is used that incorporates the Concrete Damaged Plasticity model. The linear and non-linear dynamic analysis are compared and then the sensitivity of the nonlinear dynamic analysis is discussed. The results show good agreement with the previous research using different approaches. In addition, the proposed method shows significant sensitivity to estimate damage and that it can be integrated with modal testing to assess the current condition of the structure without the need for baseline data. The mesh size effect on crack formation is also investigated.